2002
DOI: 10.3184/030823402103170501
|View full text |Cite
|
Sign up to set email alerts
|

Early Transition Metal Complexes of Polydentate and Macrocyclic Thio- and Seleno-Ethers

Abstract: Recent work on the syntheses, structures and properties of complexes of polydentate and macrocyclic thio-and seleno-ether ligands with Groups 3-6 metals in positive oxidation states (≥3) is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
(111 reference statements)
1
11
0
Order By: Relevance
“…While thioether coordination chemistry is dominated by complexes involving late transition metals in medium oxidation states, we and others have shown that under appropriate experimental conditions these soft and modest σ-donor ligands can also form complexes with hard, medium and high oxidation state early transition metal ions, [1] including for example Sc III , [2] La III and U III [3] complexes with the trithioether macrocycle [9]aneS 3 , and Ti III,IV and Cr III complexes with both acyclic and macrocyclic thioethers. [4][5][6][7] We have also established that the choice of chalcogenoether ligand architecture plays a very important role in facilitating the stabilisation of these hard/ soft metal/ligand combinations, with dimethylene-linkages between the S atoms leading to increased stability, and macrocyclic frameworks further stabilising the complexes.…”
Section: Introductionmentioning
confidence: 99%
“…While thioether coordination chemistry is dominated by complexes involving late transition metals in medium oxidation states, we and others have shown that under appropriate experimental conditions these soft and modest σ-donor ligands can also form complexes with hard, medium and high oxidation state early transition metal ions, [1] including for example Sc III , [2] La III and U III [3] complexes with the trithioether macrocycle [9]aneS 3 , and Ti III,IV and Cr III complexes with both acyclic and macrocyclic thioethers. [4][5][6][7] We have also established that the choice of chalcogenoether ligand architecture plays a very important role in facilitating the stabilisation of these hard/ soft metal/ligand combinations, with dimethylene-linkages between the S atoms leading to increased stability, and macrocyclic frameworks further stabilising the complexes.…”
Section: Introductionmentioning
confidence: 99%
“…56 The tripodal MeC(CH2EMe)3 (E = S or Se) gave 1:1 complexes on reaction with [MCl4(Me2S)2]; the complexes were too poorly soluble to grow crystals or for NMR studies and it is unclear if they are six-or seven coordinate. 50 The macrocyclic [9]aneS3 and [10]aneS3 also form poorly soluble [MCl4([n]aneS3)] complexes, but in this case the X-ray crystal structure of [ZrCl4( [9]aneS3)] was obtained ( Fig. 24) and shown to be seven-coordinate with the macrocycle  3 -coordinated.…”
Section: F-block Metal Chalcogenoether Chemistrymentioning
confidence: 99%
“…The latter will not be easy, and very meticulous care over the reaction conditions and thorough characterisation of the complexes will be essential. The problems of identifying the products of CE bond fission and ligand rearrangement observed in Nb, Ta and Mo 10,76,80,81 systems are likely to be even more challenging in the telluroether chemistry.…”
Section: Molybdenum and Tungstenmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemistry of medium and high oxidation state molybdenum and tungsten centres with neutral sulfur of oxygen donor ligands remains little studied. [74][75][76] (2) were synthesized by an analogous method to the preparation of WO 2 Cl 2 (DME) [76] (Scheme 1). (2).…”
Section: Scope and Objectives Of This Dissertationmentioning
confidence: 99%